2007
DOI: 10.1097/01.brs.0000257566.91177.cb
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy for Cervical Myelopathy due to Ossification of the Posterior Longitudinal Ligament

Abstract: Although ADF is technically demanding and has a higher incidence of surgery-related complications, it is preferable to laminoplasty for patients with occupying ratio of OPLL > or =60%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
209
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(214 citation statements)
references
References 10 publications
5
209
0
Order By: Relevance
“…2,4 Iwasaki et al reported that the surgical outcome after laminoplasty was insufficient in patients with an OPLL occupation ratio >60% and hill-shaped ossification. 1 Tani et al reported that anterior decompression surgery was superior to laminoplasty in cervical OPLL patients when their occupation ratio was more than 50%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2,4 Iwasaki et al reported that the surgical outcome after laminoplasty was insufficient in patients with an OPLL occupation ratio >60% and hill-shaped ossification. 1 Tani et al reported that anterior decompression surgery was superior to laminoplasty in cervical OPLL patients when their occupation ratio was more than 50%.…”
Section: Discussionmentioning
confidence: 98%
“…2,4 Iwasaki et al reported that the surgical outcome after laminoplasty was insufficient in patients with an OPLL occupation ratio >60% and hill-shaped ossification. 1 Tani et al reported that anterior decompression surgery was superior to laminoplasty in cervical OPLL patients when their occupation ratio was more than 50%. 4 Recent reports have described the importance of dynamic factors, including mobility of the spinal column, in the development of myelopathy in patients who have a considerable degree of canal occupation by OPLL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a series of patients with CSM due to OPLL, Iwasaki et al [25] described two shapes of anterior compressive pathoanatomy: (a) hillshaped lesions and (b) broad-based or flat lesions. In their study, Iwasaki et al found that hill-shaped lesions responded better to ventral decompression techniques whereas flat or generalized stenosis patients did as well or better with dorsal procedures such as laminoplasty [74,21,25].…”
Section: Location Of Compressive Pathologymentioning
confidence: 99%
“…In patients with primarily disc space pathology, anterior cervical discectomy will allow for adequate decompression; however, in patients with significant retrovertebral compression, an extruded migrated disc fragment, or ossification of the posterior longitudinal ligament (OPLL), corpectomy may be necessary [43]. In a series of patients with CSM due to OPLL, Iwasaki et al [25] described two shapes of anterior compressive pathoanatomy: (a) hillshaped lesions and (b) broad-based or flat lesions. In their study, Iwasaki et al found that hill-shaped lesions responded better to ventral decompression techniques whereas flat or generalized stenosis patients did as well or better with dorsal procedures such as laminoplasty [74,21,25].…”
Section: Location Of Compressive Pathologymentioning
confidence: 99%